Synergy Between Proline-Rich Antimicrobial Peptides and Small Molecule Antibiotics Against Selected Gram-Negative Pathogens in vitro and in vivo - Otvos Jr., Laszlo; Ostorhazi, Eszter; Szabo, Dora; Zumbrun, Steven D.; Miller, Lynda L.; Halasohoris, Stephanie A.; Desai, Puvi D.; Int Veldt, Sharon M.; Kraus, Carl N. (Frontiers in Chemistry, 2018)
As monotherapy, modified proline-rich antimicrobial peptides (PrAMPs) protect animals from experimental bacteremia in a dose-dependent manner. We evaluated the in vitro synergy of a modified PrAMP, A3-APO, a dimer, previously shown to inhibit the 70 kDa bacterial heat shock protein DnaK, with imipenem or colistin against two antibiotic-resistant pathogens; a carbapenemase-expressing Klebsiella pneumoniae strain K97/09 and Acinetobacter baumannii (ATCC BAA-1605). Combining antimicrobials resulted in synergy for PrAMP/colistin combination against both K. pneumoniae and A. baumannii (ΣFIC = 0.08 both) and additive activity for the A3-APO/imipenem combination against K. pneumoniae (ΣFIC = 0.53). Chex1-Arg20, (designated as ARV-1502 in preclinical development), the single chain PrAMP monomer of A3-APO, showed synergy with meropenem against a carbapenem-resistant uropathogenic Escherichia coli strain (ΣFIC = 0.38). In a murine bacteremia model using K97/09, A3-APO at 1 mg/kg demonstrated improved survival when co-administered with standard (10 mg/kg) or subtherapeutic (1 mg/kg) doses of colistin at 36 h (p < 0.05). Surprisingly, the survival benefit of A3-APO was augmented when the A3-APO dose was decreased by 50% to 0.5 mg/kg (p < 0.02) in conjunction with a subtherapeutic colistin dose (1 mg/kg). ARV-1502, as monotherapy demonstrated prolonged (> 24 hours) activity in a mouse Escherichia coli infection assay. Co-treatment with ARV-1502 and subtherapeutic doses of ceftazidime (150 mg/kg) was studied in a mouse model of melioidosis. ARV-1502 provided a 50% improvement in long-term (62 days) survival, but only at the lowest of 3 administered doses; survival advantage was demonstrated at 2.5 mg/kg but not at 5 or 10 mg/kg. The mortality benefit of combination therapies was not routinely accompanied by a parallel decline in blood or tissue bacterial counts in surviving animals, suggesting that the anti-infective activity of the host defense peptides (HDP) is broader than simply bacterial eradication. In fact, the hormetic effect observed in either animal models suggest that low dose HDP treatment may change the dominant mode of action in experimental bacteremia.